Community-acquired pneumonia: aetiology, antibiotic resistance and prospects of phage therapy. (20th August 2020) - Sheam, Md. Moinuddin; Syed, Shifath Bin; Nain, Zulkar; Tang, Swee- Seong; Paul, Dipak Kumar; Ahmed, Kazi Rejvee; Biswas, Sudhangshu Kumar
Abstract : Bacteria are the most common aetiological agents of community-acquired pneumonia (CAP) and use a variety of mechanisms to evade the host immune system. With the emerging antibiotic resistance, CAP-causing bacteria have now become resistant to most antibiotics. Consequently, significant morbimortality is attributed to CAP despite their varying rates depending on the clinical setting in which the patients being treated. Therefore, there is a pressing need for a safe and effective alternative or supplement to conventional antibiotics. Bacteriophages could be a ray of hope as they are specific in killing their host bacteria. Several bacteriophages had been identified that can efficiently parasitize bacteria related to CAP infection and have shown a promising protective effect. Thus, bacteriophages have shown immense possibilities against CAP inflicted by multidrug-resistant bacteria. This review provides an overview of common antibiotic-resistant CAP bacteria with a comprehensive summarization of the promising bacteriophage candidates for prospective phage therapy. Graphical Abstract: